Antique Glass Bottles for Essential Oils from Viminacium I - VI AD - Trifunović, Jelena; Spasić Djurić, Dragana; Krajnović, Dušanka (Archives of Pharmacy, 2022)
The archeological site Viminacium is located on the banks of the Danube near Požarevac, and represents a Roman camp and city founded in the 1st and lasted until the 7th century. It was the largest city of the Roman province of Upper Moesia. Of special significance are the discoveries from the Viminacium city, which had about 40 000 inhabitants. Glass bottles from the 1st century are few and represent the property of the first immigrants from the military and administrative apparatus. During the research of the necropolis in Viminacium, numerous glass vessels were discovered, and toilet bottles represent the most numerous and diverse group, with over eighteen types, different in size, shape of the abdomen and neck. They are made by free blowing and less often by blowing into a mold. The bottles mostly come from the graves of inhumed and cremated deceased, from the period from the end of the 1st to the beginning of the 4th century. The richness of the form, but also the simplicity of the style indicate the serial production that could have originated in Viminacium itself, while the more luxurious examples were part of the Celtic, Galician and Syrian production circles. Chemical analysis of glass bottles from Viminacium determined that the raw material for making glass mostly came from Egypt. The presence of numerous glass bottles for essential oils manifests the historical – political and economic situation, and indicates the degree of urbanization and involvement in ancient civilization.